Silicon-carbon composite negative electrode material and preparation method thereof
By using the carbon -covered nano -silicon composite material with a nuclear shell double -layer structure, the problem of insufficient capacity and volume expansion of lithium -ion battery negative materials, and realized high -energy density, stable SEI layer and excellent electrochemical properties.
Patent Information
- Application Number
- CN202411505954.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-01-28
AI Technical Summary
The graphite capacity of the negative electrode material of existing lithium-ion batteries is insufficient, and the silicon material has reduced battery performance due to volume expansion, unstable SEI growth, low conductivity and low lithium-ion diffusion coefficient.
The carbon coated nano -silicon composite material with a nuclear shell double -layer structure is used to prepare a silicon carbon composite negative material through the in situ packaging of the metal organic frame carbon layer through the combination of homemade nano -silicon core and porous non -fixed carbon layer.
By controlling the particle size uniformity and pore structure of nano -silicon particles, the expansion powder of silicon particles is relieved, and the reversible capacity maintenance rate, percentage performance and conductivity of the electrode material are improved.
Smart Images

Figure BDA0005103958360000081 
Figure BDA0005103958360000091
Abstract
Description
Technical Field
[0001] The invention relates to a silicon-carbon composite negative electrode material and a preparation method thereof, belonging to the technical field of electrode material preparation. Background Art
[0002] At present, the negative electrode material of commercial lithium-ion batteries is mainly graphite, which can accommodate lithium ions and exhibit a theoretical capacity of 372mAh / g. However, the capacity of graphite negative electrode cannot meet the market demand for large-scale application of high energy density energy storage batteries. Silicon is recognized as one of the most attractive negative electrode materials for next-generation lithium-ion batteries due to its high theoretical specific capacity of 4200mAh / g, which is more than 10 times that of traditional graphite negative electrode (372mAh / g). However, the practical application of silicon materials is largely limited by the volume expansion that causes the silicon negative electrode to pulverize, resulting in a sharp decline in battery performance, unstable SEI growth, low conductivity and low lithium ion diffusion coefficient.
[0003] In view of the above-mentioned defects, the designers have actively carried out research and innovation in order to create a silicon-carbon composite negative electrode material and a preparation method thereof, so as to make it more valuable for industrial use. Summary of the invention
[0004] In order to solve the above technical problems, the purpose of the present invention is to provide a silicon-carbon composite negative electrode material and a preparation method thereof.
[0005] A silicon-carbon composite negative electrode material of the present invention comprises a carbon-coated nano-silicon composite material having a core-shell double-layer structure;
[0006] The core structure of the carbon-coated nano-silicon composite material is a self-made nano-silicon core, and the shell layer is a porous amorphous carbon layer coated on the surface of the self-made nano-silicon core;
[0007] The raw materials for preparing the self-made nano-silicon core include acidic sulfonic acid resin, deionized water, urea, tetraethyl silicate, and magnesium acetate solution;
[0008] The raw materials for preparing the porous amorphous carbon layer include citric acid and anhydrous ethanol.
[0009] Furthermore, the self-made nano-silicon core and the amorphous carbon layer coated on the surface of the self-made nano-silicon core are combined to form a carbon-coated nano-silicon composite material with a core-shell double-layer structure, and a metal organic framework carbon layer is encapsulated in a reduction position on the surface of the carbon-coated nano-silicon composite material;
[0010] The raw materials for preparing the metal organic framework carbon layer include: polyvinyl pyrrolidone ethanol solution, 2-methylimidazole, methanol, and cobalt nitrate methanol solution.
[0011] Furthermore, the specific preparation steps are:
[0012] (1) mixing the carbon-coated nano-silicon composite material and a 1.2% polyvinyl pyrrolidone ethanol solution at a mass ratio of 1:500, stirring ultrasonically for 2 to 3 hours, and then centrifuging at a speed of 3000 r / min to obtain a precipitate, and mixing the precipitate with 2-methylimidazole and methanol at a mass ratio of 1:3:50 to obtain a mixed solution;
[0013] (2) A 3% cobalt nitrate methanol solution was rapidly injected into the above mixed solution in an equal mass ratio to generate a mixed solution, and the mixed solution was transferred to a Teflon-lined stainless steel autoclave, treated at 100-120°C for 3-4 hours, cooled to room temperature, and centrifuged to obtain a precipitate, which was washed four times with ethanol and dried in a vacuum for 10-12 hours. The obtained dry product was carbonized at 800°C for 3-4 hours in a hydrogen-argon mixed gas (vH2:vAr=5%:95%) environment to obtain a silicon-carbon composite negative electrode material.
[0014] Furthermore, the preparation steps of the carbon-coated nano-silicon composite material are:
[0015] The homemade nano-silicon core was mixed with citric acid and anhydrous ethanol in a mass ratio of 1:3:20 and then ultrasonically treated for 2 to 3 hours. The resulting suspension was dried in a vacuum drying oven at 80 to 85°C, then annealed at 800 to 850°C in a flowing argon environment for 1 to 2 hours and then cooled in a furnace under an argon flow to obtain a carbon-coated nano-silicon composite material.
[0016] Furthermore, the preparation steps of the self-made nano-silicon core are:
[0017] (1) loading the activated acidic sulfonic acid resin into a jacketed adjustable temperature distillation column, connecting the distillation column to the feed port of a reaction kettle, first adding 2000 to 2500 parts of deionized water and 7 to 10 parts of urea by weight into the reaction kettle, mixing tetraethyl silicate and water at a water-ester molar ratio of 15:1 to obtain a mixture for standby use, and simultaneously preparing a magnesium acetate solution with a mass fraction of 30%;
[0018] (2) starting stirring and heating the reactor to 80-100° C., while heating the distillation column to 60-95° C., passing the mixture and the magnesium acetate solution through the distillation column by a peristaltic pump and adding them to the reactor, keeping the temperature for 4-12 hours, and obtaining a reaction product after the reaction is completed;
[0019] (3) The reaction product was spray dried at an air inlet temperature of 115°C, an air outlet temperature of 95°C, an air inlet volume of 30-35 m3 / h, and a feed rate of 300 mL / h to obtain a self-made nano-silicon core.
[0020] By means of the above scheme, the present invention has at least the following advantages:
[0021] (1) The present invention obtains nano silicon core particles with uniform particle size by controlling the air intake of spray drying. During the spray drying process, as the air intake increases, the more heat is taken away by the airflow, the more fully the particles are dried, and thus the particle size of the sample is smaller. However, when the air intake exceeds a certain threshold, the effect on the particle size is close to critical, resulting in the particle size becoming non-uniform. Therefore, under the condition of the air intake of the present invention, uniform nano silicon particles with a particle size of 100 to 150 nm can be obtained. The higher the uniformity, the more uniform the force in the expansion process, and the less likely it is to pulverize and damage the performance of the electrode material.
[0022] (2) The present invention hydrolyzes tetraethyl silicate and magnesium acetate into a sol in a distillation column containing a sulfonic acid group in a resin, and then controls the flow rate of the sol into a reaction kettle to react with the active component set, which is more conducive to the dispersion of active sites and the formation of copper ions, thereby obtaining nano-silicon with a more uniform and rich pore structure, which can alleviate the expansion and pulverization of silicon particles, increase the specific surface area, provide a path for the penetration of electrolytes, and cooperate with the metal elements incorporated inside to significantly improve the conductivity;
[0023] (3) The present invention uses self-made nano-silicon particles as the core and a porous amorphous carbon layer formed by pyrolysis of citric acid as the shell to synthesize a carbon-coated nano-silicon composite material with a core-shell structure. As the negative electrode of a lithium-ion battery, the amorphous carbon can alleviate the silicon powdering problem, help form a stable SEI layer, and improve the reversible capacity retention rate and rate performance of the electrode material;
[0024] (4) The present invention uses polyvinyl pyrrolidone and cobalt nitrate as raw materials, and then in-situ encapsulates the metal organic framework carbon layer on the surface of the carbon-coated nano-silicon composite material, thereby further limiting the expansion of silicon particles, increasing the specific surface area, providing a path for the penetration of electrolytes, and improving conductivity to a certain extent.
[0025] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the preferred embodiments of the present invention are described in detail as follows. DETAILED DESCRIPTION
[0026] The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention.
[0027] (1) loading the activated acidic sulfonic acid resin into a jacketed adjustable temperature distillation column, connecting the distillation column to the feed port of a reaction kettle, first adding 2000 to 2500 parts of deionized water and 7 to 10 parts of urea by weight into the reaction kettle, mixing tetraethyl silicate and water at a water-ester molar ratio of 15:1 to obtain a mixture for standby use, and simultaneously preparing a magnesium acetate solution with a mass fraction of 30%;
[0028] (2) starting stirring and heating the reactor to 80-100° C., and heating the distillation column to 60-95° C., and adding the mixture and the magnesium acetate solution to the reactor through a peristaltic pump and passing through the distillation column, and keeping the mixture to react for 4-12 hours. After the reaction is completed, a reaction product is obtained; tetraethyl silicate and magnesium acetate are first hydrolyzed into a sol in a distillation column containing a sulfonic acid resin, and then flowed into the reactor at a controlled rate to react with the active component set, which is more conducive to the dispersion of active sites and the formation of copper ions, thereby obtaining nano-silicon with a more uniform and rich pore structure, which can alleviate the expansion and pulverization of silicon particles, increase the specific surface area, provide a path for the penetration of electrolytes, and cooperate with the metal elements incorporated inside to significantly improve the conductivity;
[0029] (3) The reaction product is spray dried, the air inlet temperature of the spray drying is 115°C, the air outlet temperature is 95°C, and the air inlet volume is 30-35m 3 / h, the feed rate is 300mL / h, and a self-made nano silicon core is obtained; by controlling the air intake of the spray drying, nano silicon core particles with uniform particle size are obtained. During the spray drying process, as the air intake increases, the more heat is taken away by the airflow, the more fully the particles are dried, and thus the smaller the particle size of the sample is. However, when the air intake exceeds a certain threshold, the effect on the particle size is close to critical, resulting in the particle size tending to be uneven. Therefore, under the condition of the air intake of the present invention, uniform nano silicon particles with a particle size of 100 to 150nm can be obtained. The higher the uniformity, the more uniform the force in the expansion process, and the less likely it is to pulverize and damage the performance of the electrode material.
[0030] (4) The self-made nano-silicon core, citric acid and anhydrous ethanol were mixed in a mass ratio of 1:3:20 and then ultrasonically treated for 2 to 3 hours. The obtained suspension was dried at 80 to 85°C in a vacuum drying oven, and then annealed at 800 to 850°C in a flowing argon environment for 1 to 2 hours and then cooled in a furnace under an argon flow to obtain a carbon-coated nano-silicon composite material; a carbon-coated nano-silicon composite material with a core-shell structure was synthesized using the self-made nano-silicon particles as the core and the porous amorphous carbon layer formed by the thermal decomposition of citric acid as the shell. As the negative electrode of a lithium-ion battery, the amorphous carbon can alleviate the silicon powdering problem, help form a stable SEI layer, and improve the reversible capacity retention rate and rate performance of the electrode material;
[0031] (5) the carbon-coated nano-silicon composite material obtained above and a 1.2% polyvinyl pyrrolidone ethanol solution were mixed at a mass ratio of 1:500, ultrasonically stirred for 2 to 3 hours, and then centrifuged at a speed of 3000 r / min to obtain a precipitate, and the precipitate was mixed with 2-methylimidazole and methanol at a mass ratio of 1:3:50 to obtain a mixed solution;
[0032] (6) A 3% cobalt nitrate methanol solution is rapidly injected into the above-mentioned mixed solution in an equal mass ratio to generate a mixed solution, and the mixed solution is transferred to a Teflon-lined stainless steel autoclave, treated at 100-120°C for 3-4 hours, cooled to room temperature, centrifuged to obtain a precipitate, washed with ethanol 4 times, and dried in a vacuum for 10-12 hours. The obtained dry matter is carbonized at 800°C for 3-4 hours in a hydrogen-argon mixed gas (vH2:vAr=5%:95%) environment to obtain a silicon-carbon composite negative electrode material. Then, polyvinyl pyrrolidone and cobalt nitrate are used as raw materials to perform an in-situ encapsulation of a metal organic framework carbon layer on the surface of the carbon-coated nano-silicon composite material, thereby further limiting the expansion of silicon particles, increasing the specific surface area, providing a path for the penetration of electrolytes, and improving the conductivity to a certain extent.
[0033] Example 1
[0034] (1) loading the activated acidic sulfonic acid resin into a jacketed adjustable temperature distillation column, connecting the distillation column to the feed port of a reactor, first adding 2000 parts of deionized water and 7 parts of urea to the reactor, and mixing tetraethyl silicate and water at a water-ester molar ratio of 15:1 to obtain a mixture for standby use, and simultaneously preparing a magnesium acetate solution with a mass fraction of 30%;
[0035] (2) starting stirring and heating the reactor to 80° C., while heating the distillation column to 60° C., passing the mixture and the magnesium acetate solution through the distillation column by a peristaltic pump and adding them to the reactor, keeping the temperature for 4 hours, and obtaining a reaction product after the reaction is completed;
[0036] (3) The reaction product was spray dried. The air inlet temperature of the spray drying was 115°C, the air outlet temperature was 95°C, and the air inlet volume was 30m 3 / h, the feed rate was 300mL / h, and the homemade nano-silicon core was obtained;
[0037] (4) The homemade nano-silicon core was mixed with citric acid and anhydrous ethanol in a mass ratio of 1:3:20 and then ultrasonically treated for 2 h. The obtained suspension was dried at 80 °C in a vacuum drying oven, and then annealed at 800 °C for 1 h in a flowing argon environment and then cooled in a furnace under an argon flow to obtain a carbon-coated nano-silicon composite material;
[0038] (5) the carbon-coated nano-silicon composite material obtained above and a 1.2% polyvinyl pyrrolidone ethanol solution were mixed at a mass ratio of 1:500, ultrasonically stirred for 2 hours, and then centrifuged at a speed of 3000 r / min to obtain a precipitate, and the precipitate was mixed with 2-methylimidazole and methanol at a mass ratio of 1:3:50 to obtain a mixed solution;
[0039] (6) A 3% cobalt nitrate methanol solution was rapidly injected into the above mixed solution in an equal mass ratio to generate a mixed solution, and the mixed solution was transferred to a Teflon-lined stainless steel autoclave and treated at 100°C for 3 hours. After cooling to room temperature, the precipitate was obtained by centrifugation, washed with ethanol four times, and dried in a vacuum for 10 hours. The obtained dry material was carbonized at 800°C for 3 hours in a hydrogen-argon mixed gas (vH2:vAr=5%:95%) environment to obtain a silicon-carbon composite negative electrode material.
[0040] Example 2
[0041] (1) loading the activated acidic sulfonic acid resin into a jacketed adjustable temperature distillation column, connecting the distillation column to the feed port of a reactor, first adding 2000 parts of deionized water and 7 parts of urea to the reactor, and mixing tetraethyl silicate and water at a water-ester molar ratio of 15:1 to obtain a mixture for standby use, and simultaneously preparing a magnesium acetate solution with a mass fraction of 30%;
[0042] (2) starting stirring and heating the reactor to 90° C., while heating the distillation column to 75° C., passing the mixture and the magnesium acetate solution through the distillation column by a peristaltic pump and adding them to the reactor, keeping the temperature for 8 hours, and obtaining a reaction product after the reaction is completed;
[0043] (3) The reaction product was spray dried. The air inlet temperature of the spray drying was 115°C, the air outlet temperature was 95°C, and the air inlet volume was 32m 3 / h, the feed rate was 300mL / h, and the homemade nano-silicon core was obtained;
[0044] (4) The homemade nano-silicon core was mixed with citric acid and anhydrous ethanol in a mass ratio of 1:3:20 and then ultrasonically treated for 2 h. The resulting suspension was dried in a vacuum drying oven at 83 °C, and then annealed at 830 °C for 2 h in a flowing argon environment and then cooled in a furnace under an argon flow to obtain a carbon-coated nano-silicon composite material;
[0045] (5) the carbon-coated nano-silicon composite material obtained above and a 1.2% polyvinyl pyrrolidone ethanol solution were mixed at a mass ratio of 1:500, ultrasonically stirred for 3 hours, and then centrifuged at a speed of 3000 r / min to obtain a precipitate, and the precipitate was mixed with 2-methylimidazole and methanol at a mass ratio of 1:3:50 to obtain a mixed solution;
[0046] (6) A 3% cobalt nitrate methanol solution was rapidly injected into the above mixed solution in an equal mass ratio to generate a mixed solution, and the mixed solution was transferred to a Teflon-lined stainless steel autoclave and treated at 110°C for 4 hours. After cooling to room temperature, the precipitate was obtained by centrifugation, washed with ethanol four times, and dried in a vacuum for 11 hours. The obtained dry material was carbonized at 800°C for 3.5 hours in a hydrogen-argon mixed gas (vH2:vAr=5%:95%) environment to obtain a silicon-carbon composite negative electrode material.
[0047] Example 3
[0048] (1) loading the activated acidic sulfonic acid resin into a jacketed adjustable temperature distillation column, connecting the distillation column to the feed port of a reactor, first adding 2500 parts of deionized water and 10 parts of urea to the reactor, and mixing tetraethyl silicate and water at a water-ester molar ratio of 15:1 to obtain a mixture for standby use, and simultaneously preparing a magnesium acetate solution with a mass fraction of 30%;
[0049] (2) starting stirring and heating the reactor to 100° C., while heating the distillation column to 95° C., passing the mixture and the magnesium acetate solution through the distillation column by a peristaltic pump and adding them to the reactor, keeping the temperature for 12 hours, and obtaining a reaction product after the reaction is completed;
[0050] (3) The reaction product was spray dried, the inlet temperature of the spray drying was 115°C, the outlet temperature was 95°C, and the air volume was 35m 3 / h, the feed rate was 300mL / h, and the homemade nano-silicon core was obtained;
[0051] (4) The homemade nano-silicon core was mixed with citric acid and anhydrous ethanol in a mass ratio of 1:3:20 and then ultrasonically treated for 3 h. The obtained suspension was dried in a vacuum drying oven at 85 °C, and then annealed at 850 °C for 2 h in a flowing argon environment and then cooled in a furnace under an argon flow to obtain a carbon-coated nano-silicon composite material;
[0052] (5) the carbon-coated nano-silicon composite material obtained above and a 1.2% polyvinyl pyrrolidone ethanol solution were mixed at a mass ratio of 1:500, ultrasonically stirred for 3 hours, and then centrifuged at a speed of 3000 r / min to obtain a precipitate, and the precipitate was mixed with 2-methylimidazole and methanol at a mass ratio of 1:3:50 to obtain a mixed solution;
[0053] (6) A 3% cobalt nitrate methanol solution was rapidly injected into the above mixed solution in an equal mass ratio to generate a mixed solution, and the mixed solution was transferred to a Teflon-lined stainless steel autoclave and treated at 120°C for 4 hours. After cooling to room temperature, the precipitate was obtained by centrifugation, washed with ethanol 4 times, and dried in a vacuum for 12 hours. The obtained dry material was carbonized at 800°C for 4 hours in a hydrogen-argon mixed gas (vH2:vAr=5%:95%) environment to obtain a silicon-carbon composite negative electrode material.
[0054] Example 4
[0055] The preparation steps of this embodiment are basically the same as those of embodiment 1, except that the air volume of the spray drying in step (3) is 40m 3 / h, the other preparation steps remain unchanged, and the silicon-carbon composite negative electrode material is also prepared;
[0056] Example 5
[0057] The preparation steps of this embodiment are basically the same as those of embodiment 1, except that the air volume for spray drying in step (3) is 25 m 3 / h, the other preparation steps remain unchanged, and the silicon-carbon composite negative electrode material is also prepared;
[0058] Comparison Example
[0059] Comparative Example 1
[0060] The preparation method of this comparative example is basically the same as the preparation method of Example 1, except that ordinary nano-silicon with a particle size of 100 nm is used to replace the homemade nano-silicon core of the present invention. The other preparation steps remain unchanged, and the silicon-carbon composite negative electrode material is also prepared;
[0061] Comparative Example 2
[0062] The preparation method of this comparative example is basically the same as the preparation method of Example 1, except that the porous amorphous carbon layer is not coated on the surface of the homemade nano-silicon particles. The other preparation steps remain unchanged, and the silicon-carbon composite negative electrode material is also prepared;
[0063] Comparative Example 3
[0064] The preparation method of this comparative example is basically the same as the preparation method of Example 1, except that the metal organic framework carbon layer is not in situ encapsulated on the surface of the carbon-coated nano-silicon composite material. The other preparation steps remain unchanged, and the silicon-carbon composite negative electrode material is also prepared;
[0065] The performance test experiments were carried out on Examples 1-5 of the present invention and Comparative Examples 1-3 respectively, and the specific test results are shown in Table 1:
[0066] Detection method:
[0067] The prepared Si / G composite material was used as the active material, and the conductive agent (Super P) and the binder sodium alginate were added into the stirring tank of the degassing machine in a mass ratio of 8:1:1. Polyvinyl pyrrolidone was added as the solvent. The mixture was stirred at a high speed of 2000 r / min for 1 h to obtain the negative electrode slurry, which was then evenly coated on the copper foil and transferred into a vacuum oven. The dried negative electrode sheet was baked at 80°C for 12 h to evaluate the electrochemical performance.
[0068]
[0069]
[0070] It can be seen from the test data in the above table that the negative electrode materials finally prepared in Examples 1-3 of the present invention have excellent reversible capacity retention rate, anti-powdering damage performance and conductivity, which proves that the technical solution of the present application is highly feasible;
[0071] Then, the performance of Examples 4 and 5 is compared with that of Example 1. Since the air intake of spray drying in Examples 4 and 5 is not within the specific range of the present application, the anti-pulverization stability of the final negative electrode material is significantly reduced, and various electrical properties are also reduced. It can be seen that the present invention obtains nano-silicon core particles with uniform particle size by controlling the air intake of spray drying. During the spray drying process, as the air intake increases, the more heat is taken away by the airflow, the more fully the particles are dried, and thus the smaller the particle size of the sample. However, when the air intake exceeds a certain threshold, the effect on the particle size is close to critical, resulting in the particle size tending to be uneven. Therefore, under the condition of the air intake of the present invention, uniform nano-silicon particles with a particle size of 100 to 150 nm can be obtained. The higher the uniformity, the more uniform the force in the expansion process, and the less likely it is to pulverize and damage the performance of the electrode material.
[0072] Then, the performance of the control example 1 and the embodiment 1 of the present invention is compared. Since the self-made nano-silicon kernel of the present invention is replaced by ordinary nano-silicon with a particle size of 100 nm in the control example 1, the other preparation steps remain unchanged, and the silicon-carbon composite negative electrode material is also obtained; the anti-expansion and pulverization performance of the final negative electrode material is significantly reduced, and the conductivity is also significantly reduced. It can be seen that the present invention first hydrolyzes tetraethyl silicate and magnesium acetate into a sol in a distillation column in a resin containing a sulfonic acid group, and then controls the flow rate into the reactor to react with the active component set, which is more conducive to the dispersion of active sites and the formation of copper ions, and then obtains nano-silicon with a more uniform and rich pore structure, which can alleviate the expansion and pulverization of silicon particles, increase the specific surface area, provide a path for the penetration of electrolytes, and cooperate with the metal elements incorporated inside to significantly improve the conductivity;
[0073] The performance of the control example 2 and the embodiment 1 of the present invention are compared. Since the porous amorphous carbon layer is not coated on the surface of the homemade nano-silicon particles in the control example 2, the other preparation steps remain unchanged, and the silicon-carbon composite negative electrode material is also prepared, resulting in the reduction of the anti-powdering performance, the reversible capacity retention rate and the rate performance of the final negative electrode material. It can be confirmed that the present invention uses the homemade nano-silicon particles as the core and the porous amorphous carbon layer formed by the pyrolysis of citric acid as the shell to synthesize a carbon-coated nano-silicon composite material with a core-shell structure. As the negative electrode of the lithium ion battery, the amorphous carbon can alleviate the silicon powdering problem, help to form a stable SEI layer, and improve the reversible capacity retention rate and rate performance of the electrode material;
[0074] Finally, the performance of the control example 3 of the present invention and the embodiment 1 are compared. Since the metal organic framework carbon layer is not in situ encapsulated on the surface of the carbon-coated nano-silicon composite material in the control example 3, the other preparation steps remain unchanged, and the silicon-carbon composite negative electrode material is also prepared; the collision resistance and electrical conductivity of the final negative electrode material are significantly reduced. It can be seen that the present invention uses polyvinyl pyrrolidone and cobalt nitrate as raw materials, and then in situ encapsulates the metal organic framework carbon layer on the surface of the carbon-coated nano-silicon composite material, thereby further limiting the expansion of silicon particles, increasing the specific surface area, providing a pathway for the penetration of electrolytes, and improving the conductivity to a certain extent.
[0075] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. It should be pointed out that a person skilled in the art can make several improvements and modifications without departing from the technical principles of the present invention, and these improvements and modifications should also be regarded as within the scope of protection of the present invention.
Claims
1. A silicon-carbon composite negative electrode material, characterized in that: The silicon-carbon composite negative electrode material comprises a carbon-coated nano-silicon composite material having a core-shell double-layer structure; The core structure of the carbon-coated nano-silicon composite material is a self-made nano-silicon core, and the shell layer is a porous amorphous carbon layer coated on the surface of the self-made nano-silicon core; The raw materials for preparing the self-made nano-silicon core include acidic sulfonic acid resin, deionized water, urea, tetraethyl silicate, and magnesium acetate solution; The raw materials for preparing the porous amorphous carbon layer include citric acid and anhydrous ethanol.
2. The silicon-carbon composite negative electrode material according to claim 1, characterized in that: The self-made nano-silicon core and the amorphous carbon layer coated on the surface of the self-made nano-silicon core are combined to form a carbon-coated nano-silicon composite material with a core-shell double-layer structure, and a metal organic framework carbon layer is encapsulated in a reduction position on the surface of the carbon-coated nano-silicon composite material; The raw materials for preparing the metal organic framework carbon layer include: polyvinyl pyrrolidone ethanol solution, 2-methylimidazole, methanol, and cobalt nitrate methanol solution.
3. The method for preparing a silicon-carbon composite negative electrode material according to claim 2, characterized in that: The specific preparation steps are: (1) mixing the carbon-coated nano-silicon composite material and a 1.2% polyvinyl pyrrolidone ethanol solution at a mass ratio of 1:500, stirring ultrasonically for 2 to 3 hours, and then centrifuging at a speed of 3000 r / min to obtain a precipitate, and mixing the precipitate with 2-methylimidazole and methanol at a mass ratio of 1:3:50 to obtain a mixed solution; (2) A 3% cobalt nitrate methanol solution was rapidly injected into the above mixed solution in an equal mass ratio to generate a mixed solution, and the mixed solution was transferred to a Teflon-lined stainless steel autoclave, treated at 100-120°C for 3-4 hours, cooled to room temperature, and centrifuged to obtain a precipitate, which was washed four times with ethanol and dried in a vacuum for 10-12 hours. The obtained dry product was carbonized at 800°C for 3-4 hours in a hydrogen-argon mixed gas (vH2:vAr=5%:95%) environment to obtain a silicon-carbon composite negative electrode material.
4. The method for preparing a silicon-carbon composite negative electrode material according to claim 3, characterized in that: The preparation steps of the carbon-coated nano-silicon composite material are as follows: The homemade nano-silicon core was mixed with citric acid and anhydrous ethanol in a mass ratio of 1:3:20 and then ultrasonically treated for 2 to 3 hours. The resulting suspension was dried in a vacuum drying oven at 80 to 85°C, then annealed at 800 to 850°C in a flowing argon environment for 1 to 2 hours and then cooled in a furnace under an argon flow to obtain a carbon-coated nano-silicon composite material.
5. The method for preparing a silicon-carbon composite negative electrode material according to claim 4, characterized in that: The preparation steps of the self-made nano-silicon core are: (1) loading the activated acidic sulfonic acid resin into a jacketed adjustable temperature distillation column, connecting the distillation column to the feed port of a reaction kettle, first adding 2000 to 2500 parts of deionized water and 7 to 10 parts of urea by weight into the reaction kettle, mixing tetraethyl silicate and water at a water-ester molar ratio of 15:1 to obtain a mixture for standby use, and simultaneously preparing a magnesium acetate solution with a mass fraction of 30%; (2) starting stirring and heating the reactor to 80-100° C., while heating the distillation column to 60-95° C., passing the mixture and the magnesium acetate solution through the distillation column by a peristaltic pump and adding them to the reactor, keeping the temperature for 4-12 hours, and obtaining a reaction product after the reaction is completed; (3) The reaction product was spray dried at an air inlet temperature of 115°C, an air outlet temperature of 95°C, an air inlet volume of 30-35 m3 / h, and a feed rate of 300 mL / h to obtain a self-made nano-silicon core.